Penurunan Kadar Fe Dan Mn Menggunakan Kapur Tohor (CaO) Pada Penetralan Air Asam Tambang - Yolno Vernando; Afni Nelvi; Ahmad Fadhly; Dian Hadiyansyah; Hisni Rahmi (Fakultas Teknik Universitas Panca Bhakti, 2025)
The treatment of acid mine drainage at PT Bumi Bara Makmur Mandiri is conducted using an active treatment method. It was found that there is cloudy wastewater with a brownish and reddish-brown color in the settling pond. The objective of this study was to analyze the changes in pH, Fe and Mn concentrations in acid mine drainage samples using quicklime and to calculate the cost required for neutralizing the acid mine drainage. The neutralization process was carried out on a laboratory scale using an experimental method with 3 variations of quicklime doses: 0.2 g/l, 0.3 g/l, and 0.4 g/l. The results showed that quicklime is effective in reducing Fe and Mn value in acid mine drainage. The initial pH of the acid mine drainage was 6.05. The pH increased with the increase in the quicklime coagulant dose. The Fe concentration before the neutralization of acid mine drainage was 1.20 mg/l, which decreased to 0.15 mg/L for all given dose variations. The initial Mn concentration exceeded the environmental quality standard and showed a significant reduction at a dosage of 0.2 g/L, decreasing from 72.20 mg/L to 0.08 mg/L. Similar Mn concentrations were obtained at dosages of 0.3 g/L and 0.4 g/L, each resulting in 0.122 mg/L. The cost required to neutralize Fe and Mn was IDR 368,000 per day, or IDR 11,040,000 per month.